Virtual Communities: A Global Resource - Hellenius, Shawna; Curry, Ann (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Building communities within communities has always been a public library service. Libraries have traditionally facilitated this through gatherings in library meeting rooms and dissemination of contact information about local clubs and municipal services, but virtual Internet-based communities can now provide a powerful, more wide-ranging avenue for customer to customer communication. Transaction log analysis of Internet use...